Communication Organization of "Salima Mazari" Governor Charkint Afghanistan on the Conflict Against the Taliban - Wuri Annisafitri; Ahmad Toni (KOMUNIKA: Jurnal Dakwah dan Komunikasi, 2022)
The creation of a harmonious relationship within an organization becomes the most crucial part of the process of achieving organizational goals. Cooperative relationships in an organization begin with communication and interaction between members, in addition to having an attitude of responsibility, honesty, broad-mindedness, and the courage to make decisions. Furthermore, a leader in an organization must maintain good communication skills. A similar case happened under the leadership of Salima Mazari as Governor of Charkint Afghanistan during the conflict in Afghanistan with the Taliban group. As a leader, Salima must be competent to defend her citizens and survive. Thus, communication makes it essential for Salima to communicate with government officials and the community. This study aimed to determine the communication pattern of Salima Mazari as a leader in Charkint, Afghanistan, an area that is being hit by a prolonged political conflict. The data collection method used in this research is a literature study with secondary data that discusses the managerial and leadership style of Salima Mazari as the Governor of Charkint Afghanistan during the conflict that hit Afghanistan by analyzing his motivation and leadership style. The theory used is organizational communication theory. Based on the results of this study, Salima Mazari tends to have a managerial and leadership kind of "Inviting Participants."